(3JaSjQ GdJSJQis - (3CHh eMeO Sgd Hf YHO Gddg GdJSJQj,J (B283 (3g` s
(3ChdgG (B:s
(3HYO GdHSedI CNHQfG GdTjN GdhGYX GHh fUQ CMeO Hf YHO GdLHGQ HOQ eMeO s
(3BNQgG (B:s
(3ahbaJ fGMjI MJi Oaf hJaQb GdfGS Yf bHQg ade jRd jVWQH Ydi bHQg MJi eGJ aOaf HLfHg ced cJGH GdJaSjQ s
(3HgG fXGe GdJYbjHIs
(3hYdjG ebGHdGJ hHgG JOGNd ai HYV GdUaMGJ eY HYVgG ef GdWQa fGSN Yf GdJUhjQs
(3hJfbU ef ChQGb (B36 (3, (B81 (3, (B86s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B143s
(3JHUQGJ GdCUd (B:s
Keywords: (3eJaQbGJs